The Business Case for Women's Employment in Agribusiness - International Finance Corporation (Washington, DC, 2017)
This publication aims to fill existing gaps in the literature regarding women’s paid employment in agribusiness, especially with respect to emerging economies. Women workers’ contribution to agribusiness is neither fully understood nor fully valued. The majority of research on women’s participation in agribusiness in emerging economies focuses on small-holder farming contexts, rather than direct employment relationships or women’s participation in management. Furthermore, there is limited analysis of the business gains associated with proactive interventions related to women’s employment. This publication aims to fill these gaps by: Providing a practical look at enterprise-level practices on women’s employment in agribusiness; and Considering how companies can better support women employees and how this can have a positive impact on companies’ bottom line. There is an established business case for private sector investment in women’s employment, which also applies to agribusiness. Companies that invest in women can improve their access to labor and talent, can lower the costs of recruitment and (re)training by reducing labor turnover, can drive innovation and cohesion through having a more diverse workforce and management team, and can improve productivity through stronger teams and employee motivation. Moreover, proven compliance and quality employment can improve access to quality buyers. Thus, agribusiness companies who do not invest in women are potentially missing out on important business gains, and policy-makers are missing a potential lever to open up equal opportunities, and ratchet up labor standards, to support inclusive growth for women workers in agriculture. The focus of this publication is women that are directly employed, paid labor, predominantly among larger employers. While smallholder and outgrower farming has a vital role to play in rural development, it is not the main subject here.